THE EFFECT OF CULTURE MEDIA AND ACTIVATED CHARCOAL ON ASYMBIOTIC SEED GERMINATION AND SEEDLING DEVELOPMENT OF A THREATENED ORCHID Dendrobium taurulinum J.J. Smith IN VITRO [Pengaruh Media Kultur dan Arang Aktif pada Perkecambahan Biji dan Perkembangan Seedling Anggrek Langka Dendrobium taurulinum J. J. Smith in vitro] - Siti Nurfadilah (Research Center for Biology-Indonesian Institute of Sciences, 2016)
Seed germination and seedling development are an initial and crucial stage in the plant growth and development. Many factors influence seed and seedling development. The aim of the present study was to investigate the effects of different culture media (KC, VW, and MS) and the concentration of activated charcoal (0 g/l and 2 g/l) on asymbiotic seed germination and seedling development of a threatened orchid, Dendrobium taurulinum. Results showed that germination occurred regardless of culture media type, however the percentage of seed germination was higher on media with 2 g/l activated charcoal (> 90 %) than on media without activated charcoal (0 g/l). After 12 weeks asymbiotic seed culture, seeds sown on media with 2 g/l activated charcoal grew and developed more rapidly to leaf-bearing protocorms (seedlings) compared to media without activated charcoal.The highest occurrence of advanced seedlings (stage 4, 89.77%) was observed on MS medium with 2 g/l activated charcoal.